RIFM fragrance ingredient safety assessment, 2-methyl-3-buten-2-ol, CAS Registry Number 115-18-4. (October 2015) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential as well as environmental safety. Repeated dose, developmental, and reproductive toxicities were determined to have the most conservative systemic exposure derived NO[A]EL of 50 mg/kg/day, based on OECD gavage toxicity studies in rats, that resulted in a MOE of 4545455 after considering 100% absorption from skin contact and inhalation. A MOE of >100 is deemed acceptable. Highlights: 2-Methyl-3-buten-2-ol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Repeated dose toxicity was determined to give the most conservative systemic derived NO[A]EL. An acceptable MOE was obtained.